How to make a maker librarian - Moorefield-Lang, Heather; Coker, Megan (Journal of New Librarianship, 2020)
Makerspaces are simply a location for open exploration, tinkering, problem solving, and critical thinking for all. This definition and idea ties in well to the focus of the Knowledge School. Makerspaces and the librarians who work in them aim at being socially just, community based, and focus their maker learning locations toward their practitioners. Those in schools, universities, and communities who are often charged to implement a maker location. When a student graduates from a Masters of Library and Information Science program or iSchool are they are ready to work with makers in their community? Are they ready to learn and train themselves? Are they ready to continue growth in their own knowledge? Have their programs of study, their schools of knowledge trained them appropriately? This article delves into case studies focused on that very discussion.